IMPLEMENTASI PERANCANGAN ALAT HAND WASHER DAN LIQUID SOAP BOTTLE OTOMATIS BERBASIS ARDUINO NANO ATMEGA328 - Marcelinus Petrus Saptono; Ery Murniyasih (LPPM Poltek ST Paul, 2022)
Microcontroller technology with Arduino nano as Atmega328 as a control system allows it to be implemented in an automatic faucet water system and pump soap automatically. With a dc pump motor as a soap dispenser pump. The IR obstacle sensor will get a trigger by detecting an object in front of the sensor, the input from this sensor will move the water pump sinleader motor to drain the water, using a mini water pump motor to run liquid soap under the control of the Arduino nano Atmega328. The purpose of this research is to make a tool that can help people wash their hands and place soap and water without touching them using an Arduino nano Atmega328 icrocontroller and an IR obstacle as a sensor. The results of this study are the implementation of the hand washer system and the automatic liquid soap bottle system based on the Arduino nano Atmega328 microcontroller on the sink to function properly. The IR obstacle sensor can detect objects within the sensor range, automatically responding to faucet water or soap in bottles that can come out.